Extracellular Vesicles Derived From Apoptotic Cells: An Essential Link Between Death and Regeneration - Li, Maojiao; Liao, Li; Tian, Weidong (Frontiers in Cell and Developmental Biology, 2020)
Apoptosis is a universal and continuous event during tissue development, restoration, repair, and regeneration. Mounting evidence has demonstrated that apoptosis is essential for the activation of tissue regeneration. However, the underlying mechanism remains elusive. A striking development in recent years comes from research on extracellular vesicles (EVs) derived from apoptotic cells. During apoptosis, cells secrete vesicles of various sizes containing various components. Apoptotic cell-derived EVs (ApoEVs) have been found to transit to neighboring cells or cells in distant tissues through the circulation. These vesicles could act as containers to transmit the nucleic acid, protein, and lipid signals to target cells. ApoEVs have been shown to promote regeneration in the cardiovascular system, skin, bone, muscle, kidney, etc. Moreover, several specific signalling pathways mediating the anabolic effects of ApoEVs have been classified. In this review, we comprehensively discussed the latest findings on the function of ApoEVs in tissue regeneration and disease prevention. These findings may reveal unexpected clues regarding the regulatory network between cell death and tissue regeneration and suggest novel targets for regenerative medicine. The findings discussed here also raise the question whether and to what extent ApoEVs contribute to embryonic development. This question is all the more urgent because the exact functions of apoptotic events during numerous development processes are still largely unclear.